Strategy of Integrating Pluralism Values in The Development of Inclusive Curriculum in Educational Institutions - Shofiyyah, Nilna Azizatus; Deni Miharja (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
inclusive curricula in educational institutions, focusing on the formation of inclusive and responsive learning environments for diverse students' needs. The research method employed is qualitative research with a literature study approach. This approach involves in-depth analysis of relevant literature sources such as academic journals, books, and scholarly articles related to pluralism, inclusive curriculum, and strategies for integrating pluralism values in the educational context. The findings indicate that incorporating pluralism values into an inclusive curriculum positively impacts shaping students' attitudes, values, and understanding of cultural diversity and differences. Concrete steps such as selecting learning materials that reflect diversity, involving stakeholders, teacher training, and utilizing technology effectively support efforts to create inclusive learning environments. In this context, teacher training plays a key role in the successful implementation of an inclusive curriculum, while the use of technology serves as an innovative tool to enhance learning flexibility and accessibility. The conclusion of this research reflects that integrating pluralism values into an inclusive curriculum not only has a strong moral and ethical foundation but also represents a strategic investment in creating equitable and relevant education for all students. This research contributes to a deep understanding of adaptive strategies for developing inclusive curriculum, detailing the role of pluralism values as key drivers in shaping a generation ready to face the increasing complexity of a diverse global society.